Wannier–Stark electro-optical effect and photonic modes in 2D macroporous silicon structures with SiO₂ nanocoatings - Karachevtseva, L.; Goltviansky, Yu.; Kolesnyk, O.; Lytvynenko, O.; Stronska, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We have investigated the IR light absorption oscillations in 2D macroporous
silicon structures with SiO₂ nanocoatings, taking into account the Wannier–Stark electrooptical
effect caused by a strong electric field on the Si-SiO₂ boundary and an additional
electric field of quasi-guided optical modes. The photonic modes and band gaps were
also considered as peculiarities in absorbance spectra of macroporous silicon structures
with a thick SiO₂ nanocoating. The photonic modes do not coincide with the quasiguided
modes in the silicon matrix.